The Mediating Roles of Upward Social Comparison and Self-esteem and the Moderating Role of Social Comparison Orientation in the Association between Social Networking Site Usage and Subjective Well-Being - Wang, Jin-Liang; Wang, Hai-Zhen; Gaskin, James; Hawk, Skyler (Frontiers in Psychology, 2017)
The increased pervasiveness of social media use has raised questions about potential effects on users’ subjective well-being, with studies reaching contrasting conclusions. To reconcile these discrepancies and shed new light on this phenomenon, the current study examined: (1) whether upward social comparison and self-esteem mediate the association between social networking site (SNS) usage and users’ subjective well-being, and (2) whether the association between SNS usage and upward social comparison is moderated by users’ social comparison orientation. Data from 696 participants were collected. Structural equation modeling revealed that upward social comparison and self-esteem mediated the relationship between SNS usage and users’ subjective well-being. We found that social comparison orientation moderated the association between passive SNS usage and users’ upward social comparison. Specifically, social comparison orientation strengthened the association between passive SNS usage and upward social comparison. The results might suggest a process through which passive SNS usage is related to subjective well-being, and identify a context under which these associations may differ.